Blockchain based optimal decision making of dispatchable units in smart grids considering the high uncertainty effects. (January 2022) - Zhu, Xiangqian; Wang, Wenfeng; Pang, Suhong; An, Chaoyin; Yang, Xiaoliang; Wu, Yanmin
Highlights: The proposed mechanism can provide lower steady state error and Total Harmonic Distortion (THD) with faster response compare to traditional controller. The novel controller can coordinate within microgrids to maintain stability in the islanded mode. The proposed controller can secure the network by avoiding malicious attacks with novel block-chain framework. Abstract: Using blockchain technology (BCT) in securing data has received a lot of attention these days. This technology is used not only as a new way with the aim of enhancing the cyber and physical security of power systems, but also has been applied to enhance the exchanged information between units. When Fuel Cell (FC), photovoltaic cells (PV) and wind turbines (WT) are used as sources of distributed generation (DG), there will be a situation called Islanding Micro-Grid (MG), so that this situation has the ability to control voltage, frequency and current of the system with no dependence on the utility. Hence, for overcoming load variations and disturbances, designing and implementing a robust controller is vital. Accordingly, a robust General Type-2 Fuzzy sliding mode controller (GT2FSMC) on the basis of gray wolf optimization algorithm is presented in the following study with the purpose of enhancing the power sharing amongst the distributed generations operating in the off-grid MG. The offered controller, in addition to warrant the stability and robust versus uncertainties of the lumped generated via extrinsic disturbances and un-modelled dynamics, has the ability to significantly decrease the control chattering inherent in primary sliding mode control. In the following paper, it is assumed that there are two distributed generations, each with specific duties. One has the duty of regulating the frequency and voltage through a reference signal, and another is responsible for working in load current control mode with the aim of sharing load correctly among each of them. For stopping malicious attacks, an assured policy framework according to the blockchain (BC) has been created to enhance the security of interchanged data among production units. Plus, two low-voltage parallel DG units exist in the MG. With the aim of evaluating the mentioned way, the simulation results have been done via MATLAB environment. According to the outcomes, it can be concluded that this mentioned controller has the ability of providing lower steady state error and Total Harmonic Distortion (THD) with faster response in comparison to the further controllers that generally are used. The simulation results show that the DG unit operations within the islanding MG have the ability of coordinating successfully under that mentioned control system with the aim of confirming stable operation of the throughout MG.